Sistem Informasi Geografis Daerah Penangkapan Ikan di Perairan Natuna-Laut Cina Selatan Berbasis Data Satelit NOAA/AVHRR dan SEAWIFS - Yus Sholva (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Satellite remote sensing can be used to detect oceanographic phenomenon such assea-surface temperature (SST), chlorophyll concentration, and sea current. UsingNOAA/AVHRR and SeaWiFS satellites, the parameters to estimate potential fishing zone(PFZ) such sea-surface temperature and chlorophyll concentration can be derived from thedata of them.This research had been taken place in Natuna Sea-South China Sea. Both sea-surfacetemperature and chlorophyll concentration parameters are used to develop potential fishingzone. Having information of coordinate, the fish catch data are used to determine the optimalfishing zone by using the spatial analysis. At that time, historical fish catch data is use toanalyze potential fishing by seasons.A geographic information system (GIS) model has been developed to achieve the goal.By this approach, the processing of satellite data, fish catch data, and other statistic is easierto manage. GIS modelling provides a powerful tool for fish forecasting and sustainablemanagement of living marine resources. With this tool and its provided-coordinate, catchingfish process will be efficient and effective.Preliminary results of the research show that most potential season for fishing isduring Transition Period I (March – June). While based on monthly approach, the mostpotential months for fishing are during April, May, and August.Keywords: remote sensing, sea surface temperature, chlorophyll, potential fishing zone,and spatial analysis.